2020
DOI: 10.1002/jcp.29894
|View full text |Cite
|
Sign up to set email alerts
|

Irisin deficiency disturbs bone metabolism

Abstract: Balancing the process of bone formation and resorption is important in the maintenance of healthy bone. Therefore, the discovery of novel factors that can regulate bone metabolism remains needed. Irisin is a newly identified hormone-like peptide. Recent studies have reported the involvement of irisin in many physiological and pathological conditions with bone mineral density changes, including osteopenia and osteoporotic fractures. In this study, we generated the first line of Osx-Cre:FNDC5/ irisin KO mice, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 66 publications
2
47
1
Order By: Relevance
“…Both groups ( 26 , 75 ) note that their results—that irisin inhibits bone formation—are the opposite of Colaianni et al ( 114 , 122 ). They did not reference the results of other groups who also found irisin enhanced bone formation ( 120 , 124 , 125 ). Estell et al ( 75 ) suggested that the opposite effects of irisin (inhibition vs enhancement of bone formation) might be due to the concentration of irisin and the duration or frequency of application.…”
Section: Physiological Roles Of Irisinmentioning
confidence: 85%
See 1 more Smart Citation
“…Both groups ( 26 , 75 ) note that their results—that irisin inhibits bone formation—are the opposite of Colaianni et al ( 114 , 122 ). They did not reference the results of other groups who also found irisin enhanced bone formation ( 120 , 124 , 125 ). Estell et al ( 75 ) suggested that the opposite effects of irisin (inhibition vs enhancement of bone formation) might be due to the concentration of irisin and the duration or frequency of application.…”
Section: Physiological Roles Of Irisinmentioning
confidence: 85%
“…In another recent study, Zhu et al ( 125 ) performed a selective KO of FNDC5 in bone cells using an osterix-Cre driver. Osterix-Cre has been used to knock out genes specifically in osteoblasts and osteocytes.…”
Section: Physiological Roles Of Irisinmentioning
confidence: 99%
“…FNDC5 signaling components play an important role in mediating the beneficial effects that physical activity and moderate exercise evoke, maintaining intracellular homeostasis and metabolism so as to stifle senescence programs, degeneration processes and inflammatory reactions in various tissues in aging, overweight and diabetic conditions [37]. The myokine also communicates via the muscle-bone axis pathway to regulate bone mineral acquisition and osteoporosis development [38], as well as orchestrating muscle-kidney interplay to control renal anabolism and nephropathy [39]. Of interest, regular moderate exercise is found to alleviate joint pain and severity of OA, improving the kinematic activity of injured knees and hips [1].…”
Section: Discussionmentioning
confidence: 99%
“…ese effects improve the WAT metabolic profile and enhance whole-body energy expenditure, making irisin a potential new therapeutic target for the treatment of obesity and its complications. More recent studies have shown that irisin also plays a potential role in bone metabolism [11,12], including improving osteoblastogenesis [13][14][15] and enhancing bone mass and bone mineral density (BMD) [16,17] in many physiological and pathological conditions. e relevance of irisin in humans has also been demonstrated [18][19][20].…”
Section: Introductionmentioning
confidence: 99%